REKAYASA PERANCANGAN SISTEM INFORMASI POSYANDU (Studi Kasus di Desa Samarang Kec. Samarang) - Ramdhani Hidayat (Masoem University, 2019)
Posyandu is one form of Community-based Health Efforts (UKBM) that are managed and organized from, by, for and with the community in the implementation of health development. Yandu Post has an important role in providing information about the demographics of the community in a rural area, this is only conveyed through the form of records in tiered reporting so that information that should be absorbed quickly by policy makers requires considerable time. Along with the development of increasingly rapid technology with the development of increasingly sophisticated hardware it is necessary to report for the Yandu post blinded by an application that can accelerate the flow of information for those who are solid and have policies.Engineering and designing an information system for these needs is an absolute thing that must be immediately realized so that reporting can immediately be used by people who have interests and policies in making decisions so that there are no more problems that can occur due to lack of speed in taking action to finish. The results of the engineering design of the system in the form of an Android-based application because Android is already a common item that almost all people have. Information systems can control the implementation of the work and the implementation function by producing information according to predetermined provisions.